Relating management problem-solving styles of leaders to TQM focus: an empirical study. Issue 2 (13th March 2017) - Kumar, Vimal; Sharma, R.R.K.
Abstract : Purpose: The purpose of this paper is to develop a relationship between the leader's management problem-solving styles (MPSS) and total quality management (TQM) focus. Design/methodology/approach: The study is based on C.G. Jung's (1923) four psychological functions or cognitive styles, which are involved in information gathering and evaluation by sensing, intuitive, thinking, and feeling. The combination of these psychological functions makes possible ways of results: sensing-thinking (ST), sensing-feeling (SF), intuitive-thinking (NT), and intuitive-feeling (NF) for management problem solving. The empirical data for this study were drawn from a survey of 111 firms in India. A one-way analysis of variance approach has been applied for analysis in this study. Findings: The authors review the extant literature and present a conceptual framework to establish the relationship between different management problem-solving styles and TQM focus. The literature on TQM shows two distinct achievable results: continuous improvement and innovation. The findings of the study support all the hypotheses and the results show that leaders with ST and SF profile are comfortable with the continuous improvement while leaders with NT and NF profile focus on innovation in the organization. Practical implications: The results of this study emphasize the importance of knowing the appropriate MPSS to TQM focus. The results will help leaders in continuous improvement and innovation to make proper decisions and smooth functions to achieve maximum performance. Originality/value: This paper can be useful for the organizations to achieve more effective leadership in decision making and improve perception-information model as a leader's cognitive style. Moreover, this paper also attempts to inspire researchers to include the cognitive styles in studying the effect of the leaders on TQM focus while implementing it effectively in the organizations.